Contributions of forensic anthropology to positive scientific identification: a critical Review - Douglas H. Ubelaker; Austin Shamlou; Amanda Kunkle (Oxford University Press, 2019)
This review covers previous and current literature on the impact of forensic anthropologists on the positive scientific identification of human remains and aims to provide an understanding of what information a forensic anthropologist can contribute to an investigation. Forensic anthropologists looking to identify human remains study traits of the skeleton and any orthopedic devices present. In order to obtain a positive scientific identification, evidence that is both sufficiently unique to the individual and comparable to available antemortem data from that individual must be found. The increased availability of radiographs, scans and implants in recent decades has facilitated the identification process. When these records are unavailable, other techniques, such as craniofacial superimposition and facial approximation, can be employed. While these methods may assist the identification process, they are most useful for exclusion of certain individuals and gathering leads from the public. Forensic anthropologists have heavily relied on the skull and its complexities for identification - typically focusing on the frontal sinus and other unique traits. Post-cranial remains can provide important information about bone density, possible disease and other characteristics that may also be utilized. Techniques used to positively identify individuals are not limited to medicolegal death investigations, and have been useful in other legal contexts. In the future, a team approach, utilizing all the information gathered by multiple forensic scientists - including forensic anthropologists - will most likely become more common.